METABOLIC DISORDERS IN PATIENTS WITH HIGH RISK FOR RECURRENT URINARY TRACT STONES - JAMAL, MR; ADNAN, M; MUZAMMIL, M; REHMAN, RAU; ULLAH, S; AHMAD, I (Biological and Clinical Sciences Research Journal, 2023)
A cross-sectional study was conducted to assess the frequency of metabolic disorders detected in 24-hour urine collection in patients with increased morbidity for recurrent upper urinary tract stones. This research was conducted Department of Urology Bakhtawer Amin Hospital, Multan. Study was carried out over a period of six months from 01-12-2021 to 01-06-2022. Total 100 cases presented with the recurrent urinary tract stone were enrolled in this study. Patients were asked about their demographics which include name, age, gender and contact details. A 24-hour urine sample from each patient was analyzed for its contents. Metabolic abnormalities were recorded as per operational definition) . Out of 100 patients, 30 %( n=30) were in age Group of 12-30 years whereas 70 %(n=70) were in age Group of 31-60 years, mean age was calculated as 35.85 ± 9.83 years. Mean duration of kidney stone was 1.69 ± 0.46 months. Frequency of metabolic abnormalities were 42%. We concluded that, the most common 24-hour urine abnormalities were hyperuricosuria (32%), hypercalciuria (19%), hypernatriuria (20%).